Aura Magika / Angelin Floren - Floren, Angelin (2022)
The task given by my lecturer was to do business individual as part of my assignment. I decided to be an agent of Aura Magika which deal with product including lotion and health supplement. For your information. Aura Magika was established in 2012 and it is located at Jalan 2, 68100 Kuala Lumpur, Malaysia. Moreover, Aura Magika product known for it’s ability to overcome the problem of back and waist pain and also helps to ensure the smooth the blood’s journey. As a preference, I would like to market the product using online method through social media. It is easier to deal with customers since you just need to advertise the products name and it’s benefits. Furthermore, this online method does not required your time to visit your customers place. All the product details and contact number will be provided. As an agent I will get the benefits from the sales of the product through sales commission. Lastly, I hope my goals will be achieve and be able to accomplish my mission as a successful agent of Aura Magika.